2011
DOI: 10.1002/rcm.5035
|View full text |Cite
|
Sign up to set email alerts
|

Lipid fingerprinting of Gram‐positive lactobacilli by intact cells – matrix‐assisted laser desorption/ionization mass spectrometry using a proton sponge based matrix

Abstract: A method of direct lipid analysis by matrix-assisted laser desorption/ionization (MALDI) mass spectrometry (MS) in intact membranes, without prior extraction/separation steps, is described. Here, we demonstrate the efficacy of a strong base, 1,8-bis(dimethylamino)naphthalene (DMAN; proton sponge), as a novel matrix for MALDI-time-of-flight (TOF) MS analysis of whole cell bacteria. Initially, individual acidic low-molecular-weight analytes such as standard free fatty acids and phospholipids were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…The experimental results show that the mass spectra obtained with chloroform/methanol as the extraction solvent present more mass peaks. The lipid profiles of the bacteria obtained in the experiment are basically consistent with previously reported profiles obtained using the traditional MALDI methods [15,36,38,39].…”
Section: Resultssupporting
confidence: 88%
“…The experimental results show that the mass spectra obtained with chloroform/methanol as the extraction solvent present more mass peaks. The lipid profiles of the bacteria obtained in the experiment are basically consistent with previously reported profiles obtained using the traditional MALDI methods [15,36,38,39].…”
Section: Resultssupporting
confidence: 88%
“…The methods used for L. acidophilus were thin layer chromatography and low-resolution fast atom bombardment mass spectrometry (Fernández Murga et al, 2001). The present study is one of only a few studies using mass spectrometry to identify the lipid species, and previously none of them have used state-of-the-art high-resolution FTMS-based lipidomics (Calvano et al, 2011;Drucker et al, 1995;Fernández Murga et al, 2001). Further studies using high-resolution MS techniques will show if the present findings can be generalized beyond L. acidophilus La-5.…”
Section: Discussionmentioning
confidence: 97%
“…The lipid classes included the lipids identified in another study of L. acidophilus (Fernández Murga et al, 2001), and additionally identified MLCL, PA and QGDG, but not diglycodiacylglycerol (DGDG). DGDG could be an intermediate for TGDG and QGDG, as the glycosyltransferase responsible for transferring glyco-residues is able to transfer up to four residues to the precursor, diacylglycerol (Hölzl & Dörmann, 2007 have not been identified in other lipid studies on Lactobacillus species (Calvano et al, 2011;Drucker et al, 1995;Exterkate et al, 1971;Fernández Murga et al, 2001;Machado et al, 2004;Murga et al, 2000;Tymczyszyn et al, 2005). One reason for this difference could be that the composition of the lipid classes is dependent on the bacterial species and strain and only one research group has investigated the lipid classes of the L. acidophilus species within the last 15 years (Fernández Murga et al, 2001;Murga et al, 2000), and this was not the same strain as L. acidophilus La-5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, MALDI MS has become a technique of considerable impact on many fi elds, from proteomics [ 11 , 12 ] to lipidomics [ 13 , 14 ] and, more recently, even metabolomics due to the introduction of new matrices such as ionic liquids [ 15 , 16 ], proton sponges [ 17 ] or aromatic amines [ 18 ], and metal nanoparticles [ 19 , 20 ].…”
Section: Food Analysis By Mass Spectrometrymentioning
confidence: 99%